Yunpi Heluo decoction reduces ectopic deposition of lipids by regulating the SIRT1-FoxO1 autophagy pathway in diabetic rats. (31st December 2022) - Mao, Zhujun; Liu, Shiyu; Yu, Tao; Su, Jinglan; Chai, Kefu; Weng, Siying
Abstract: Context: Yunpi Heluo (YPHL) decoction is a Chinese herbal formula with particular advantages for treating type 2 diabetes. Yet, its exact mechanism of action is not fully understood. Objective: To examine the therapeutic effect of YPHL on ectopic lipid deposition (EDL) in Zucker diabetic fatty (ZDF) rats and the underlying mechanism. Materials and methods: The ZDF Rats were randomized into five groups, including model, YPHL (200 mg/kg/d for 10 weeks), SIRT1-overexpression (injected with HBAAV2/9-r-SIRT1-3′-flag-GFP), NC (injected with HBAAV2/9-CMV-GFP as blank control) and control group. Pancreatic β-cells obtained from high-lipid-high-glucose fed rats were treated with YPHL (10 mg/mL) for 48 h. Lipid deposition and autophagosomes were analyzed by transmission electron microscopy. Intracellular H2 O2 and ROS concentrations were measured by flow cytometry. SIRT1, FOXO1, LC3 and P62 mRNA and protein levels were analyzed using qRT-PCR and Western blots. Results: Compared with the model group, blood glucose levels in YPHL and si-SIRT1 groups were reduced by 19.3% and 27.9%, respectively. In high-lipid-high-glucose cells treated with YPHL, lipid droplets were reduced and decrease in apoptosis rate (38.6%), H2 O2 (31.2%) and ROS (44.5%) levels were observed. After YPHL intervention or SIRT1 overexpression, LC3 and p62 expression increased. Protein expression of SIRT1 and LC3 in model, si-SIRT1, si-NC and si-SIRT1 + YPHL groups was lower than those in control group, while FoxO1 expression was increased. All of these protein level alterations were reversed in the si-NC + YPHL group. Discussion and conclusions: YPHL reduced EDL by regulating the SIRT1-FoxO1 autophagy pathway in diabetic rats, which could lead to future perspectives for the treatment of diabetes.